Activation of Glycolysis by MCM10 Increases Stemness and Paclitaxel Resistance in Gastric Cancer Cells - Wu, Zhangqiang; Fang, Yuejun; Wu, Jun; Wang, Jianjun; Ling, Yingjie; Liu, Tao; Tong, Qin; Yao, Yefeng (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Chemotherapy is an essential avenue for curing malignancies; however, tumor cells acquire resistance to chemotherapeutic agents, eventually leading to chemotherapy failure. At present, paclitaxel (PTX) resistance seriously hinders the therapeutic efficacy of gastric cancer (GC). Investigating the molecular mechanism of PTX resistance in GC is critical. This study attempted to delineate the impact of MCM10 on GC resistance to PTX and its mechanism in GC. Materials and Methods: The expression of minichromosome maintenance complex component 10 (MCM10) in GC tissues, its enrichment pathways, and its correlation with glycolysis marker genes and stemness index (mRNAsi) were analyzed in a bioinformatics effort. Real-time quantitative polymerase chain reaction was used to assay the expression of MCM10 in cells. Cell counting kit-8 (CCK-8) was used to analyze cell viability and calculate the 50% inhibitor concentration (IC50) value. Western blot was used to measure the expression of MCM10, Hexokinase 2 (HK2) and stemness-related factors in cells. Sphere-forming assay was performed to study cell sphere-forming ability. Seahorse XF 96 was utilized to measure cell extracellular acidification and oxygen consumption rates. The content of glycolysisrelated products was tested with corresponding kits. Results: MCM10 was significantly upregulated in GC and enriched in the glycolysis pathway, and it was positively correlated with both glycolysis-related genes and stemness index. High expression of MCM10 increased sphere-forming ability of drug-resistant cells and GC resistance to PTX. The stimulation of PTX resistance and drug-resistant cell stemness in GC by high MCM10 expression was mediated by the glycolysis pathway. Conclusion: MCM10 was upregulated in GC and drove stemness and PTX resistance in GC cells by activating glycolysis. These findings generated new insights into the development of PTX resistance in GC, implicating that targeting MCM10 may be a novel approach to improve GC sensitivity to PTX chemotherapy. Cite this article as: Wu Z, Fang Y, Wu J, et al. Activation of glycolysis by MCM10 increases stemness and paclitaxel resistance in gastric cancer cells. Turk J Gastroenterol. 2023;34(11):1107-1115.